(untitled) (Baghdad Science Journal, 2013)
In this work the design and construction of optical pumping system was presented. The parameters of the pumping source to obtain discharge current density sufficient to shift the flash lamp spectrum towards uv portion of spectrum were measured.The current density was supplied to the flash lamp must be greater than 4000Amp./cm2 to obtain the spectral range wavelength lies between 0.2 and 0.35?m. The current density was obtained by a capacitor 50?F, at 7KV discharge voltage. The applied electrical energy to the flash lamp was more than 1200 J, and the current density was around 5000 Amp./cm2.The electrical parameters of the flash lamp were calculated. The impedance parameters(K0) from the voltage and the peak current pulse was measured in range equal to 57, while the damping factor(?) was 1.3. The energy of the flash lamp was around 75% from the input electrical energy. The external trigger circuit was limited the increase the applied voltage, which is responsible for the damping factor.